Effect of Ethanol Extract of Sea Pandan Fruit (Pandanus Tectorius) on Blood Glucose Levels in Male White Rats (Rattus Norvegicus) Induced by Dexamethasone - Ghifara Kireina Annisa; Nita Pranitasari; R. Varidianto Yudo Tjahjono; Roostantia Indrawati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Diabetes mellitus is a metabolic disorder with increased blood glucose due to decreased insulin production or sensitivity. Chronic hyperglycemia can lead to endothelial dysfunction and vascular complications. Dexamethasone as a synthetic glucocorticoid can cause hyperglycemia through increased gluconeogenesis and insulin resistance. The antioxidant content in sea pandanus (Pandanus tectorius) has the potential to lower blood glucose levels. This study aims to determine the effect of ethanol extract of sea pandan fruit on blood glucose levels of male white rats (Rattus norvegicus) induced by dexamethasone. This study aims to determine the effect of ethanol extract of sea pandan fruit (Pandanus tectorius) on blood glucose levels in male white rats (Rattus norvegicus) induced by dexamethasone. Experimental research with a post test only control group on 30 mice grouped into 3 groups. Namely, K(-) which was only given standard feed, K(+) which was induced by dexamethasone at a dose of 5 mg/KgBB, and KP which was induced by dexamethasone at a dose of 5 mg/KgBB and given Pandanus tectorius fruit extract at a dose of 100 mg/KgBB, then at the end of the study a blood sample was taken to measure blood glucose levels and then terminated. The sample was selected using simple random sampling technique. The data was analyzed using the One Way Anova test. In the results of the study, the average blood glucose level K(-) = 170.37 was obtained; K(+) = 274.62; KP = 243. In the One Way Anova parametric test, a significant result was obtained which was 0.005 (p<0.05). Then in the Post Hoc Games-Howell test, K(-) and K(+) had a significance of 0.001 (p<0.05), while the K(-) and KP groups as well as K(+) and KP showed no significant results. This suggests that ethanol extract of Pandanus tectorius fruit did not successfully inhibit the increase in blood glucose levels in dexamethasone-induced white rats. The administration of ethanol extract of Pandanus tectorius fruit as a therapy was able to reduce the blood glucose level of male Rattus norvegicus induced by dexamethasone compared to a K(+) positive control of 31.62 mg/dL (11.5%).